We advance in health thanks to the PAPI children's health application - Concepción Sánchez Pina; Jaime Javier Cuervo Valdés; Javier Garrido Torrecillas; María Isabel Martín Delgado; Olga Cortés Rico; María Jesús Esparza Olcina; José María Mengual Gil (Elsevier, 2023)
Introduction: The family structure and parenting are changing in society, sedentary lifestyle, the use of screens and social networks is increasing. Families and health professionals must learn to educate, adapting their health advice to the new social and digital environment. Materials and methods: A survey was sent to the representatives of more than 5000 paediatricians to renew the Well Child Visits Programme of the Spanish Association of Primary Care Paediatrics (AEPap). Contributions from preventive programmes from Andalusia, the Balearic Islands and Asturias were incorporated. The different interventions and advice were distributed in nine age groups. Results: Part of the recommendations are based on the work of the PrevInfad group. It uses the methodology of evidence-based medicine and performs the evaluation and synthesis of the evidence in the proposed preventive activities.The AEPap considers that the Well Child Programme should be carried out by the paediatric team: the paediatrician and the nurse, thus enhancing specific skills.The WHO considers it essential to empower individuals, families, and communities to optimize their health by making them caretakers of themselves and others, equipping them with tools that protect their well-being. Conclusion: Hence, it was decided to capture the Well Child Programme in the format of a free APP for mobile devices, as an innovative and affordable method of disseminating child and adolescent health. Information is given on parenting advice for family members, for children and adolescents and describes health check-ups for health workers. Resumen: Introducción: La estructura familiar y la crianza están cambiando en la sociedad, se incrementa el sedentarismo, el uso de pantallas y de redes sociales. Las familias y los profesionales sanitarios deben aprender a educar, adaptando sus consejos de salud al nuevo entorno social y digital. Material y métodos: Para renovar el Programa de Salud Infantil (PSI) de la Asociación Española de Pediatría de Atención Primaria (AEPap) se envió una encuesta a los representantes de más de 5.000 pediatras. Se incorporaron aportaciones de los programas preventivos de Andalucía, Baleares y Asturias. Se distribuyeron las diferentes intervenciones y consejos en nueve grupos etarios. Resultados: Parte de las recomendaciones están basadas en el trabajo del grupo PrevInfad, llevadas a cabo con metodología de medicina basada en la evidencia, mediante la evaluación y síntesis de la evidencia de las actividades preventivas propuestas.La AEPap considera que el PSI debe realizarse por el equipo de pediatría: pediatra y enfermera/o, potenciándose así las competencias específicas.La OMS considera primordial empoderar a las personas, familias y comunidades para que optimicen su salud al convertirlas en cuidadoras de sí mismas y de otros, dotándolas de herramientas que protegen el bienestar. Conclusiones: Por todo ello se decide plasmar el PSI en formato de APP para dispositivos móviles gratuita, como método innovador y asequible de divulgación de salud infantojuvenil. Se informa sobre consejos de crianza para los familiares, para los niños/as y adolescentes y describe las revisiones de salud para los sanitarios.